Characterization of genetic variants of vulnerability to epilepsy in Algerian families - Amina Chentouf; Mohand Laid Oubaiche; Malika Chaouch (Journal de la Faculté de Médecine d'Oran, 2022)
Objectives - This study aims to investigate the surrounding family when several cases of epileptics are found, the goal is to establish inheritance patterns and to identify genetic variants and to document the genotype/phenotype correlation. Materials and methods - Affected members from extended families with familial epilepsy were assessed at the University Hospital of Oran between December 2011 and December 2016. All participants underwent neurological examination, EEG and brain MRI. Epileptic syndromes have been classified according to the International League Against Epilepsy (LICE) criteria, and the modes of inheritance have been established through genealogical analysis. After genomic DNA extraction, genetic variants of susceptibility to epilepsy were investigated by comparative genomic hybridization on DNA microarrays (CGH-array) and next-generation sequencing (NGS). Results - Sixty-five epileptic families participated in this study. The mean age of seizure  onset was 9.5 ± 6.1 years with a slight male predominance (sex ratio: 1.35). 50% had generalized seizures and 40% experienced focal seizures. The consanguinity rate among parents of affected was 50% with phenotypic concordance observed in 2/3 of families. According to pedigree analysis, epilepsy was inherited in an AD mode with or without reduced penetrance in 29 families (44.6%) and AR mode in 23 families (35.4%). Genetic analyzes have identified mutations in the EPM1 gene in patients with progressive myoclonic epilepsy, a mutation in the RELN gene in individuals with temporal lobe epilepsy and schizophrenia, and both benign and pathogenic CNVs. In addition, a de novo mutation (p.A39E) in the GAL gene was identified in monozygotic twins with temporal lobe epilepsy. Functional analysis strongly supports GAL as the causal gene for the TLE in this family. Conclusion - This study described the epileptic phenotype and determined the mode of transmission of epilepsy in large multigenerational Algerian families, and identified known genetic variants but also interesting neomutations.